Nonlinear Analysis on Flutter of Functional Graded Cylindrical Panels on Elastic Foundations Using the Ilyushin Nonlinear Supersonic Aerodynamic Theory - Quan, Tran Quoc; Bich, Dao Huy; Duc, Nguyen Dinh (VNU Journal of Science: Mathematics - Physics; Vol 31 No 2, 2015)
Based on classical shell theory with the geometrical nonlinearity in von Karman-Donell sense and the Ilyushin nonlinear supersonic aerodynamic theory, this paper successfully formulated the equations of motion of the functionally graded cylindrical panel on elastic foundations under impact of a moving supersonic airflow and found the critical velocity of supersonic airflow that make the panel unstable. This paper also used the Bubnov-Galerkin and Runge – Kutta methods to solve the system of nonlinear vibration differential equations and illustrated effects of initial dynamical conditions, shape and geometrical parameters, material constituents and elastic foundations on aerodynamic response and instability of FGM cylindrical panel. Keywords: Nonlinear flutter, the Ilyushin supersonic aerodynamic theory, functional graded cylindrical panel, elastic foundations.